Sociality Affects REM Sleep Episode Duration Under Controlled Laboratory Conditions in the Rock Hyrax, Procavia capensis - Gravett, Nadine; Bhagwandin, Adhil; Lyamin, Oleg I.; Siegel, Jerome M.; Manger, Paul R. (Frontiers in Neuroanatomy, 2017)
The rock hyrax, Procavia capensis, is a highly social, diurnal mammal. In the current study several physiologically measurable parameters of sleep, as well as the accompanying behaviour, were recorded continuously from five rock hyraxes, for 72 h under solitary (experimental animal alone in the recording chamber), and social conditions (experimental animal with 1 or 2 additional, non-implanted animals in the recording chamber). The results revealed no significant differences between solitary and social conditions for total sleep times, number of episodes, episode duration or slow wave activity (SWA) for all states examined. The only significant difference observed between social and solitary conditions was the average duration of rapid eye movement (REM) sleep episodes. REM sleep episode duration was on average 20 sec and 40 sec longer under social conditions daily and during the dark period, respectively. It is hypothesized that the increase in REM sleep episode duration under social conditions could possibly be attributed to improved thermoregulation strategies, however considering the limited sample size and design of the current study further investigations are needed to confirm this finding. Whether the conclusions and the observations made in this study can be generalised to all naturally socially sleeping mammals remains an open question.